The effect of mental training associated with the practice of technique using a visual technique (3D VR) and acoustic insulation in the development of some boxing motor abilities in the team of the Faculty of Physical Education and Sports Science - Abbas, ElafRabeea (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in the use of the technique of mental training techniques (3D VR) and audio insulation at a level that supports the learning of some basic boxing skills using various exercises and tools in the method of mental training as well as the use of glasses (3D VR) and audio insulation. The problem of research came from the field observation of the researcher and his follow-up to the methods of boxing. Traditional methods are often used to learn skills and lack diversity using methods. This may lead to boredom and boredom among the learners, as well as lack of use of mental training in learning motor skills by teaching, boxing that the student did not have a clear picture of the typical performance of the overall skill. The aim of the research was to identify the effect of the technique of mental training using 3D VR technique and the acoustic isolation in learning some basic boxing skills. As for the imposition of the research, there are statistically significant differences between the results of the tribal and remote testing of the experimental research group in learning some basic boxing skills. The researcher used the experimental method to design a single group with the same tribal and remote tests in order to suit the nature of the research problem. The research community is a boxing player in the College of Physical Education and Sports Science, which consists of 13 boxers. In light of the findings the researcher has concluded. The mental training works to develop the motor precision and motor compatibility of Iraq’s youth in boxing. The researcher recommended paying attention to mental training as a training tool that complements the physical, skill, and plan preparation and attributes these exercises.